REVITALISASI POSYANDU REMAJA UNTUK MEMBANGUN GENERASI SEHAT DI PADUKUHAN PULUHAN LOR, TRIMURTI, SRANDAKAN, BANTUL - Imaniar Ranti; Harumi Iring Primastuti; Merita Arini (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Adolescents are a group of society that is prone to various health risks. Padukuhan Puluhan Lor has an inactive youth posyandu (integrated health post). Inadequate resources inhibit youth posyandu activities. This community service aimed to increase adolescents' knowledge and skills in health checks and posyandu management to reactivate youth posyandu. One action research cycle includes diagnosis, planning, action, and assessment. The assessment used in-depth interviews with the hamlet, community health workers, and the youth organization manager. In the action stage, educational intervention, and cadre training were conducted using a quasi-experiment (without control, non-randomization) on adolescent cadres (n=17). Cadres were coached and trained using educational media, including pocketbooks and role play. The assessment revealed that the community needs to revitalize youth posyandu, although no youth health program exists. The planning stage was to prepare education, cadre training, and posyandu equipment and materials funds. The role-play increased knowledge and skills in conducting health checks and managing posyandu based on the average score. However, there was no significant difference in teenage knowledge scores (p=0.564) before and after the education session. Youth empowerment potential can supports the implementation of youth posyandu. Cross-sectoral roles are needed to keep posyandu sustainable.